Pengaruh Profitabilitas, Kompensasi Rugi Fiskal dan Kepemilikan Asing Terhadap Penghindaran Pajak (Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2020 - 2023) - Dewi, Tasya Puspa; Yoshida, Debbie (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to test empirically the effect of profitability, fiscal loss compensation and foreign ownership on tax avoidance. The data used in this study is secondary data in the form of financial reports of food and beverage companies reported to the IDX from 2020-2023 on the website (www.idx.co.id). The sample in this study consisted of 15 food and beverage companies from 26 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. Sampling was carried out using purposive sampling method. The analysis used in this study is multiple linear regression analysis managed through SPSS. The conclusion of this study is that profitability has a negative effect on tax avoidance. Fiscal loss compensation and foreign ownership do not affect tax avoidance efforts. This research contributes to the literature on corporate tax behavior and offers insights for policymakers and stakeholders in assessing the determinants of tax compliance.